Design Principles for Thriving in Our Digital World: A High School Computer Science Course. (July 2016) - Veletsianos, George; Beth, Bradley; Lin, Calvin; Russell, Gregory
Thriving in Our Digital World is a technology-enhanced dual enrollment course introducing high school students to computer science through project- and problem-based learning. This article describes the evolution of the course and five lessons learned during the design, development, implementation, and iteration of the course from its first through third year of implementation. The design principles that we describe have guided our design endeavors and may be helpful to instructional designers, learning technologists, and others who are engaged in the design and development of in situ interventions to improve the teaching and learning of computer science.